Downregulation of IRF2 Alleviates Sepsis-Related Acute Kidney Injury in vitro and in vivo - Zhang Y; Zhang Y; Yang A; Xia F (Dove Medical Press, 2021)
Yanyan Zhang, Yun Zhang, Aixiang Yang, Fei Xia Department of Critical Care Medicine, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou, 215008, Jiangsu, People's Republic of ChinaCorrespondence: Fei XiaDepartment of Critical Care Medicine, The Affiliated Suzhou Hospital of Nanjing Medical University, No. 242, Guangji Road, Suzhou, 215008, Jiangsu, People's Republic of ChinaEmail feixia199107@163.comObjective: We investigated the roles and mechanisms of IRF2 in sepsis-related acute kidney injury (S-AKI) in a lipopolysaccharide (LPS)-induced HK-2 cell line and caecal ligation and puncture (CLP)-induced IRF2−/− mouse model.Methods: Quantitative real-time polymerase chain reaction assay was used to detect IRF2 in the serum of S-AKI patients and LPS-induced HK-2 cells. Cell proliferation, death, and apoptosis were analysed by CCK-8, lactate dehydrogenase release, and flow cytometry assays, respectively. The levels of interleukin (IL)-1β, IL-18, IL-6, tumour necrosis factor (TNF)-α, non-canonical inflammasomes, including caspase-4 and gasdermin-D (GSDMD), and canonical inflammasomes, such as caspase-1, NLR family pyrin domain containing 3 (NLRP3), and apoptosis-associated speck-like protein (ASC) in S-AKI cells or animal models were analysed by enzyme-linked immunosorbent assay or Western blotting.Results: IRF2 was upregulated in the serum of S-AKI patients and LPS-induced HK-2 cells. IRF2 downregulation promoted cell proliferation and inhibited cell death and apoptosis, respectively. IRF2 inhibition reduced the levels of IL-1β, IL-18, IL-6, and TNF-α in S-AKI cells and animal models. IRF2 knockdown inhibited LPS-treated HK-2 cell pyroptosis by decreasing the expression of caspase-4 and GSDMD, instead of affecting caspase-1, NLRP3, and ASC. An elevated survival rate and alleviated pathological features and scores were observed in the CLP-induced IRF2−/− animal models. IRF2 deficiency also suppressed inflammation and pyroptosis by inhibiting non-canonical inflammasomes as indicated by the decreased expression of caspase-11 and GSDMD.Conclusion: Our findings suggest that IRF2 downregulation protects against S-AKI in vitro and in vivo.Keywords: sepsis acute kidney injury, IRF2, inflammation, pyroptosis